La labor de las Juntas Vecinales de Tarapoto y el aporte para la Seguridad Ciudadana, en el marco de la Constitución - Mirano Apaza, Alex Saturnino (2019)
ABSTRACT The present work deals with the work that the Neighborhood Security Councils of the city of Tarapoto are doing and how they contribute to Citizen Security from a Constitutional Perspective, while the purpose is to know how these social organizations are organized, what activities they carry out, how they perform them and what results they obtain, in this way to know if all this strengthens or not the Public Safety. For the development of the research, it has been necessary to address conceptual aspects of Citizen Security, from an international and national perspective; Secondly, community participation in crime prevention has been analyzed, based on the historical experience of the countries of the United States, Mexico, Colombia and Chile, experiences collected by the CRIMINALITY REVIEW, ANALYSIS AND DEEPENING by Catalina Bello Montes and LATIN AMERICAN PROGRAM SPECIAL REPORT, on citizen participation and perception of insecurity in Latin America, AUGUST 2006 by Jessica Varat and Allison Garland; third, historical data has been taken into account, regarding the first neighborhood citizen security organizations in the nineties, that is, before the Peruvian government assumed the national agreement in 2003 on the seventh policy of state "Eradication of Violence and Strengthening Citizenship and Citizen Security", Throughout the investigation, one of the main results obtained was the fact that the authorities of the Judiciary, Public Ministry, Ministry of Health and Education do not lend support in interest in the Neighborhood Boards and as a conclusion we have the fact that these civil organizations have been developing progressively from 2005 to 2018, as such through joint work with their authorities, contributing and contributing to the strengthening of citizen security.